2013
DOI: 10.4021/wjon657w
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Imaging Modalities in the Evaluation of Vascular Invasion in Pancreatic Adenocarcinoma: A Meta-Analysis

Abstract: BackgroundThe extent of vascular invasion is a key factor determining the resectability of non-metastatic pancreatic adenocarcinoma. The purpose of this study is to determine the diagnostic accuracy of computed tomography (CT), endoscopic ultrasound (EUS), and magnetic resonance imaging (MRI) in the pre-operative evaluation of vascular invasion in pancreatic adenocarcinoma, with surgery as the reference standard.MethodsA search of the MEDLINE database for relevant articles in the English language published bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…IDRFs should be evaluated by CT or MRI with multiplanar techniques. Results of a meta-analysis showed that CT is superior to the evaluation of vascular involvement [20]. MRI is more accurate than CT for the analysis of spinal canal extension [3,21].…”
Section: Discussionmentioning
confidence: 99%
“…IDRFs should be evaluated by CT or MRI with multiplanar techniques. Results of a meta-analysis showed that CT is superior to the evaluation of vascular involvement [20]. MRI is more accurate than CT for the analysis of spinal canal extension [3,21].…”
Section: Discussionmentioning
confidence: 99%
“…There are several published data regarding the performance of endoscopic ultrasound (EUS) in showing vascular invasion in pancreatic cancers. [3][4][5][6][7][8] In a single, head-to-head comparison study of EUS and CT, EUS showed a sensitivity and specificity of 61.1% and 90.3%, respectively which was higher than CT alone. [7] This finding was also confirmed by a systematic review, which yielded the area under the curve values of EUS and CT as 0.9379 and 0.8589, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[8] However, in other meta-analyses and reviews, this superiority was not found. [4][5][6] Invasion of great mediastinal/hilar vessels in lung cancer is an important issue in identifying T component of Tumor, Node, Metastasis (TNM) staging. To date, contrast-enhanced CT has been the main modality used for assessing vascular invasions.…”
Section: Discussionmentioning
confidence: 99%
“…In meta-analyses, the pooled sensitivity and specificity were 66-86% and 89-94%, respectively [128][129][130]. The sensitivity of EUS is different for different vessels being over 80% for evaluation of portal vein invasion, consistently superior to CT-scan; for the evaluation of the superior mesenteric vein, superior mesenteric artery and celiac artery, the sensitivity of EUS is lower than CT [131][132][133]. CE-EUS increases the sensitivity of detection of PV involvement up to 100%.…”
Section: Introduction and Background: Eus For Pancreatic Cancermentioning
confidence: 99%